Exports of vegetables from India: An economic analysis - Mohandas, K.; Indhusree, A.; Kuruvila, Anil (Journal of Tropical Agriculture, 2018)
The study analyses the export performance of vegetables from India in terms of instability and concentration and also the major Non-Tariff Measures (NTMs) that limit India’s export prospects. The export of vegetables has grown significantly during the period from 1988 to 2016, both in quantity and value terms. Onion ranked top among all the major vegetables exported from India both in terms of quantity and value and the country accounted for 9.4 per cent share in the world export of onions. The export of the major vegetables from India also showed declining instability and increasing commodity as well as geographic diversification. The most stable markets for major vegetables exported from India were Nepal, Belgium, Pakistan, Mauritius, Oman, UAE, Sri Lanka and Bangladesh. Major NTMs include differential Maximum Residue Limits (MRLs) for pesticides, equivalence agreement on organic products, protocol on phyto-sanitary measures and organic certification mostly required by the developed countries, which are to be negotiated strategically for better export prospects and sustainability. The inherent issues on the supply side also need to be addressed for maintaining the already achieved growth in the export of vegetables.